2017
DOI: 10.1097/mbc.0000000000000602
|View full text |Cite
|
Sign up to set email alerts
|

Exposure of fibrinogen and thrombin to nitric oxide donor ProliNONOate affects fibrin clot properties

Abstract: Background Fibrin fibers form the structural backbone of blood clots. The structural properties of fibrin clots are highly dependent on formation kinetics. Environmental factors such as protein concentration, pH, salt and protein modification, to name a few, can affect fiber kinetics through altered fibrinopeptide release, monomer association and/or lateral aggregation. Objective To determine the effect of thrombin and fibrinogen exposed to nitric oxide on fibrin clot properties. Methods ProliNONOate (5 μM… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 45 publications
1
13
0
Order By: Relevance
“…To further explore potential applications of combined nitrite/far red light treatment, we examined clotting in platelet poor plasma. Although the main effects of NO on clotting are known to be through its action as an anti-platelet agent, a few reports have shown effects on thrombin and fibrinogen [62] , [63] . We did not observe any significant effects on the clot lysis time or maximum optical density (data not shown), but we did observe effects of nitrite and light on clotting lag time (time to reach 5% increase in OD, after initiating clotting with thrombin).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…To further explore potential applications of combined nitrite/far red light treatment, we examined clotting in platelet poor plasma. Although the main effects of NO on clotting are known to be through its action as an anti-platelet agent, a few reports have shown effects on thrombin and fibrinogen [62] , [63] . We did not observe any significant effects on the clot lysis time or maximum optical density (data not shown), but we did observe effects of nitrite and light on clotting lag time (time to reach 5% increase in OD, after initiating clotting with thrombin).…”
Section: Resultsmentioning
confidence: 99%
“…Motivated by the dramatic enhancement by far red light on RBC-mediated inhibition of platelet activation by nitrite, we explored whether nitrite and far red light treatment might have other potential benefits related to treating thrombosis. Potential of NO to treat thrombosis is primarily through its action in reducing platelet activation [5] , [75] , [76] , [77] , [78] , however, recent work suggests that it will also affect other aspects of clotting [62] . Previously, it was found that adding NO to thrombin and/or fibrinogen decreases the rate of fibrin fiber formation with consequentially lower fibrin fiber density and forming thicker fibers [62] .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…While Jana et al linked E 3 to increased fibrinolytic potential of platelet rich clots it should be noted that in our investigation platelet poor plasma was used where no platelets were present (Jana et al, ). Helms et al showed that exposure of fibrinogen and thrombin to a nitric oxide donor resulted in plasma clots with thicker fibers with a decreased density (Helms et al, ). This is contradictory to our results, therefore we can assume that the changes associated with E 1 and E 3 addition to platelet poor plasma are not to be attributed to nitric oxide influence or that these hormones can increase the fibrinolytic potential of fibrin clots in the absence of platelets.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the exposure of FB to ProliNONOate, a donor of NO, affects the structural formation of the fibrin clot, resulting in lower density, but thicker fibers [41]. Such structural variations can have significant impact on embolization and fibrinolysis, where the platelets can retract low density more than high density fibrin fibres [42].…”
Section: The Interaction Between No and Fbmentioning
confidence: 99%